INFLUENCE OF SAFETY PROMOTION ON WORK SAFETY FOR TENANT PERSONNEL IN THE TERMINAL AREA OF MINANGKABAU INTERNATIONAL AIRPORT - Andy Putra Pratama Imran, Muh.; Hartono; Rozi, Fahrur (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2025)
This study aims to determine the effect of safety promotion on occupational safety for tenant personnel in the Minangkabau International Airport terminal area. This study uses a quantitative approach with a descriptive method. Data was collected through the distribution of questionnaires to 38 respondents, who were representatives from each active tenant in the terminal area. The instruments used were validated and tested for reliability, then analyzed using the KolmogorovSmirnov normality test, Pearson correlation test, and simple linear regression test with the assistance of SPSS version 25. The results of the study indicate that safety promotion has a positive and significant effect on workplace safety. This is evidenced by a constant value of 4.338, a regression coefficient of 1.157, a calculated t-value of 9.261, and a significance level of 0.000, indicating that the effect is statistically significant. The R Square value of 0.704 indicates that 70.4% of the workplace safety variable is influenced by the safety promotion variable.